Respuesta :
Answer:
1. -1/28
2. -4
3.A) The attendance increased by an average of 25 people per game from game 2 to game 5.
4. -.125
Step-by-step explanation:
To find the rate of change, we use the formula
f(x2) - f(x1)
--------------
x2-x1
1.
f(x) = -(x) ^ 1/3
f(64) = -(64) ^ 1/3 = -4
f(8) =- (8)^1/3 = -2
f(64) - f(8) -4--2 -4+2 -2 -1
-------------- = --------- = ------------- = ----------- = ------
64 - 8 56 56 56 28
2.
f(2) = 9
f(-2) = 25
f(x2) - f(x1) f(2) - f(-2) 9-25 -16 -16
-------------- =----------- = ----------------- = ---------- = ----------- = -4
x2-x1 2--2 2+2 4 4
3.
f(5) = 755
f(2) = 680
f(x2) - f(x1) f(5) - f(2) 755-680 75
-------------- = ---------- = -------------- = ---------- = 25
x2-x1 5-2 3 3
A) The attendance increased by an average of 25 people per game from game 2 to game 5.
4.
f(-1) = -.25
f(1) = -.5
f(x2) - f(x1) f(1) - f(-1) -.5 --.25 -.5+.25 -.25
-------------- = ---------- = -------------- = ---------- = --------- = -.125
x2-x1 1--1 1+1 2 2
Answer with explanation:
We know that average of a function from x=a to x=b is calculated by:
[tex]\dfrac{f(b)-f(a)}{b-a}[/tex]
Ques 1)
[tex]f(x)=-\sqrt[3]{x}[/tex]
[tex]f(8)=-\sqrt[3]{8}\\ \\f(8)=-2[/tex]
and
[tex]f(64)=-\sqrt[3]{64}\\ \\f(64)=-4[/tex]
Hence, the rate of change from 8 to 64 is given by:
[tex]=\dfrac{-4+2}{64-8}\\\\=\dfrac{-2}{56}\\\\=\dfrac{-1}{28}[/tex]
Hence, the rate of change is:
[tex]\dfrac{-1}{28}[/tex]
Ques 2)
The table is given as:
x f(x)
-2 25
-1 24
0 21
1 16
2 9
3 0
Hence, the average rate of change from -2 to 2 is calculated as:
[tex]=\dfrac{f(2)-f(-2)}{2-(-2)}\\\\\\=\dfrac{9-25}{4}\\\\=\dfrac{-16}{4}\\\\=-4[/tex]
Hence, average rate of change is:
[tex]-4[/tex]
Ques 3)
Game Attendance (number of people)
1 654
2 680
3 702
4 732
5 755
The average rate of change from game 2 to game 5 is calculated as:
[tex]=\dfrac{755-680}{5-2}\\\\\\=\dfrac{75}{3}\\\\=25[/tex]
Hence, option: A is the correct answer.
A) The attendance increased by an average of 25 people per game from game 2 to game 5.
Ques 4)
We are asked to find the average rate of change from -1 to 1.
We have the x and y value as follows:
x y=f(x)
-2 -0.2
-1 -0.25
0 -0.33
1 -0.5
2 -1
Hence, the average rate of change from x= -1 to x=1 is calculated as:
[tex]=\dfrac{f(1)-f(-1)}{1-(-1)}\\\\\\=\dfrac{-0.5-(-0.25)}{1+1}\\\\\\=\dfrac{-0.25}{2}\\\\=-0.125[/tex]
Hence, the average rate of change from x=-1 to x=1 is:
[tex]-0.125[/tex]